Combination of protein and cell internalization SELEX identifies a potential RNA therapeutic and delivery platform to treat EphA2-expressing tumors - Laura Santana-Viera; Justin P. Dassie; Marta Rosàs-Lapeña; Silvia Garcia-Monclús; Mariona Chicón-Bosch; Marina Pérez-Capó; Lidia del Pozo; Sara Sanchez-Serra; Olga Almacellas-Rabaiget; Susana Maqueda-Marcos; Roser López-Alemany; William H. Thiel; et al. (Elsevier, 2023)
The EphA2 receptor tyrosine kinase is overexpressed in most solid tumors and acts as the major driver of tumorigenesis. In this study, we developed a novel approach for targeting the EphA2 receptor using a 2'-fluoro-modified pyrimidine RNA aptamer termed ATOP. We identified the ATOP EphA2 aptamer using a novel bioinformatics strategy that compared aptamers enriched during a protein SELEX using recombinant human EphA2 and a cell-internalization SELEX using EphA2-expressing MDA231 tumor cells. When applied to EphA2-expressing tumor cell lines, the ATOP EphA2 aptamer attenuated tumor cell migration and clonogenicity. In a mouse model of spontaneous metastasis, the ATOP EphA2 aptamer slowed primary tumor growth and significantly reduced the number of lung metastases. The EphA2 ATOP aptamer represents a promising candidate for the development of next-generation targeted therapies that provide safer and more effective treatment of EphA2-overexpressing tumors.